Low Dose Mineralocorticoid Receptor Blockade Prevents Western Diet-induced Arterial Stiffening in Female Mice - DeMarco, Vincent G. (Hypertension, 2015)
Women are especially predisposed to development of arterial stiffening secondary to obesity due to consumption of excessive calories. Enhanced activation of vascular mineralocorticoid receptors impairs insulin signaling, induces oxidative stress, inflammation and maladaptive immune responses. We tested whether a sub-pressor dose of mineralocorticoid receptor antagonist, spironolactone (1 mg•kg(−1)•day(−1)) prevents aortic and femoral artery stiffening in female C57BL/6J mice fed a high fat/high sugar western diet (WD) for four months (i.e., from 4–20 weeks of age). Aortic and femoral artery stiffness were assessed using ultrasound, pressurized vessel preparations and atomic force microscopy. WD induced weight gain and insulin resistance compared to control diet-fed mice and these abnormalities were unaffected by spironolactone. Blood pressures and heart rates were normal and unaffected by diet or spironolactone. Spironolactone prevented WD-induced stiffening of aorta and femoral artery as well as endothelial and vascular smooth muscle cells within aortic explants. Spironolactone prevented WD-induced impaired aortic protein kinase B/endothelial nitric oxide synthase signaling, as well as, impaired endothelium-dependent and –independent vasodilation. Spironolactone ameliorated WD-induced aortic medial thickening and fibrosis and the associated activation of the pro-growth extracellular receptor kinase 1/2 pathway. Finally, preservation of normal arterial stiffness with spironolactone in WD-fed mice was associated with attenuated systemic and vascular inflammation and an anti-inflammatory shift in vascular immune cell marker genes. Low-dose spironolactone may represent a novel prevention strategy to attenuate vascular inflammation, oxidative stress, and growth pathway signaling and remodeling to prevent development of arterial stiffening secondary to consumption of a WD.